Fostering intimacy on TikTok: a platform that 'listens' and 'creates a safe space'. - Şot, İrem (Media, Culture & Society, 2022)
This research explores how and why TikTok users from Turkey choose to make TikTok content. Drawing from the concept of polymedia and debates on digital connection and disconnection, which center on individuals' choices whether to connect or detach from digital media based on the affordances they offer, the article highlights an affordance shaping users' choices of media that have not received sufficient emphasis in these discussions: namely, the ability of a platform to foster intimacy. Based on qualitative research combining structured and semistructured interviews with 14 individuals, the article discusses how and why TikTok has come to be perceived either as an object of attachment with which individuals have intimate relations or as a site for individuals to fashion a shared sense of intimate, safe space with other users. I also illustrate that the ways individuals talk about intimacy intersect with how they talk about the algorithmic systems. Combining approaches from critical algorithm studies, media choices, and research on mediated intimacies, the article demonstrates that (a) individuals choose TikTok to foster intimacies and (b) users connect seemingly contradictory concepts of intimacy and algorithms in their choices of TikTok.